An Experimental Investigation and Modelling of Friction Stir Processing - WĘGLOWSKI, Marek Stanisław; HAMILTON, Carter Benjamin (Engineering Transactions, 2014)
In this paper experimental and numerical modelling of the Friction Stir Processing tech- nique are presented. The experiments were carried out on cast aluminium alloy AlSi9Mg. A conventional tool without a pin was used. During the trials, the tool temperature, torque and forces acting on the tool were measured. The results revealed that an increase in the rota- tional speed caused an increase in the temperature and a decrease in the torque. Furthermore, the increase in travelling speed caused a decrease in the tool temperature and an increase in the torque. The experimental results were compared with that achieved based on the numerical modelling.